Differential diagnosis of neurological diseases of small ruminants - GIADINIS (Ν.Δ. ΓΙΑΔΙΝΗΣ) N. D.; POLIZOPOULOU (Ζ.Σ. ΠΟΛΥΖΟΠΟΥΛΟΥ) Z. S.; FTHENAKIS (Γ.Χ. ΦΘΕΝΑΚΗΣ) G. C. (Journal of the Hellenic Veterinary Medical Society, 2017)
Objective of the present review is the description of diagnostic approach in neurological cases in small ruminants. To improve description purposes in the present paper, neurological disorders of small ruminants are classified as follows: (a) congenital neurological disorders (vitamin A deficiency, copper deficiency, disorders of viral aetiology [including border disease and Schmallenberg disease], disorders with a genetic background), (b) acquired neurological disorders with an acute course (acute coenurosis, Aujeszky’s disease, bacterial meningoencephalitis, botulism, copper deficiency, copper poisoning, disorders following injury, hypocalcaemia, hypomagnesaemia, listeriosis, louping-ill, rare disorders of parasitic aetiology, pregnancy toxaemia, rabies, tetanus, tick paralysis, toxicoses, type D enterotoxaemia, vitamin B1 deficiency) and (c) acquired neurological disorders with a long-standing course (caprine arthritis-encephalitis, central nervous system abscesses, chronic coenurosis, neoplastic disorders, ovine lentiviral encephalomyelitis, scrapie).